Affectivity in LA: Vygotsky’s ideas in the acceptance of new paradigms - Rolando, Rodolfo Meissner; Silva, Elisabeth Ramos da; Abud, Maria José Milharezi (The ESPecialist, 2025)
This art This text presents a bibliographical research, of a qualitative nature, whose objective was to investigate the relationships between the studies of Applied Linguistics and Vygotskian conceptions about the role of affectivity in human development. Therefore, it is not a question of considering affectivity only as a vector capable of boosting motivations, nor of understanding it as affective bonds between individuals. It is about assuming the dialectical integration between cognition and affectivity, as Vygotski considered. Therefore, the paths taken by Applied Linguistics were investigated, with the socio-interactionist perspective as its fulcrum, and articles were collected in magazines that adopted Vygotskian paradigms. From the year 2000 until the first half of 2024, 19 articles were found, which denotes that Applied Linguistics embraced the affectivity’s role according to Vygotski’s assumptions.